2021
DOI: 10.1371/journal.pone.0249112
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between poor reading skills, bullying and victimization across the transition from elementary to middle school

Abstract: Students with poor reading skills and reading difficulties (RDs) are at elevated risk for bullying involvement in elementary school, but it is not known whether they are at risk also later in adolescence. This study investigated the longitudinal interplay between reading skills (fluency and comprehension), victimization, and bullying across the transition from elementary to middle school, controlling for externalizing and internalizing problems. The sample consists of 1,824 students (47.3% girls, T1 mean age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 96 publications
0
3
0
1
Order By: Relevance
“…One possible reason is that previous research investigating LD as a childhood bullying risk factor did not always take psychiatric comorbidity into account. The few existing studies found that children with LD and psychiatric comorbidity (e.g., LD and ADHD) are at a higher risk of victimization [ 42 ], and of being bullies and bully-victims [ 47 , 48 ]. However, these studies did not examine all bullying roles (i.e., only victim, only bully, or bully-victim), or did not examine the effect of difficulties in different learning domains (i.e., reading, spelling, and math).…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason is that previous research investigating LD as a childhood bullying risk factor did not always take psychiatric comorbidity into account. The few existing studies found that children with LD and psychiatric comorbidity (e.g., LD and ADHD) are at a higher risk of victimization [ 42 ], and of being bullies and bully-victims [ 47 , 48 ]. However, these studies did not examine all bullying roles (i.e., only victim, only bully, or bully-victim), or did not examine the effect of difficulties in different learning domains (i.e., reading, spelling, and math).…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that high-SES children might have a greater degree of achievement pressure, as well as emotional and physical isolation from their parents, which can cause psychosocial maladjustment and internalizing health problems, such as anxiety and depression [ 36 , 37 ], with the potential to create a downward spiral of isolation, maladjustment, and internalizing problems. A growing body of evidence suggests that maladjustment and internalizing issues might predict bullying perpetration [ 17 , 38 41 ], and therefore, it could have increased the risk of perpetrating bullying among high-SES adolescents. Further research is needed to explore this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…There is not much previous research on recognizing the relationship between bullying and citizenship-related issues. More often, attention has been paid to other issues, for example, gender differences, where the percentage of girls in the profile of victims of severe harassment was higher (Jiménez, 2019), achievement in general (Al-Raqqad et al, 2017), or reading skills (Turunen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%